Silicate Liquid Immiscibility within the Crystal Mush: Late-stage Magmatic Microstructures in the Skaergaard Intrusion, East Greenland - Holness, M. B.; Stripp, G.; Humphreys, M. C. S.; Veksler, I. V.; Nielsen, T. F. D.; Tegner, Christian (Journal of Petrology, 2011)
Late-stage microstructures developed during the last stages of solidification of the Skaergaard intrusion comprise a wide array of reactive and non-reactive intergrowths. Reactive microstructures ascribed to open-system behaviour include serrated grain boundaries between pyroxene and plagioclase primocrysts, fish-hook pyroxenes and mafic symplectites. They form by the addition of Fe and Ca and removal of alkalis and silica. Other microstructures include those formed by (internally generated) redox reactions between olivine, Fe–Ti oxides and pyroxene. Non-reactive microstructures include closely spatially associated granophyric intergrowths and previously undescribed ilmenite-rich intergrowths that are interpreted as a consequence of crystallization of separated conjugate immiscible liquids. The open-system reactive microstructures occur predominantly in the cumulates on the chamber floor, appearing in LZb and disappearing (to be replaced by a granophyre–ilmenite-rich intergrowth association) in the Upper Zone. They are not common in the Marginal Border Series. Their distribution mirrors that of efficient expulsion of trapped liquid and can be attributed to the gravitationally driven loss of a Si-rich immiscible component from the interstitial liquid. The loss of the Si-rich component causes the remaining Fe-rich liquid to react with the primocrysts. Bulk-rock major element data are consistent with little or no preferential loss of the Si-rich liquid from the mush, but the resolution of the available data is not sufficient to assess the effect of this relative movement on the liquid line of descent of the bulk magma. The first appearance of the paired conjugate non-reactive intergrowths in MZ* (Marginal Border Series) points to the early onset of immiscibility in the bulk liquid.